POLITICAL AND SOCIOLOGICAL ANALYSIS OF CONTEMPORARY PROBLEMS OF INTERNATIONAL TERRORISM COUNTERACTION - V. P. Miletsky; R. S. Churina (Дискурс, 2017)
This article is devoted to the analysis of modern theoretical and practical problems of international terrorism counteraction. Special attention is paid to more precise definition of specific character of international terrorism, determination of purposes of its existence and spread, socio-psychological and international political aims of terrorist acts organizers. In conclusion a number of practical recommendations for improving the mechanism of international terrorism counteraction in the twenty-first century are proposed.